The Defence of the Long Walls of Thrace (Μακρά Τείχη τῆς Θρᾴκης) under Justinian the Great (527–565 A.D.) - Wiewiorowski, Jacek (Studia Ceranea, 2012)
The paper discusses the question of the defence of the Long Walls of Thrace (Μακρά Τείχη τῆς Θρᾴκης) or the Anastasian Wall (Αναστάσειο Τείχος) under Justinian the Great (527–565 A.D.). Emperor Anastasius I (491–518 A.D.) probably put an end to the vicarius Thraciarum, the head of administration of the late Roman Diocese of Thrace, establishing two vicars instead. One of them was responsible for the defence of the Long Walls of Thrace while the other was a purely civil officer. Both vicars governed the area of the Anastasian Wall also in the first years of Justinian’s reign. This administrative framework was useful for the defence of Constantinople itself but it also gave rise to certain problems. When Justinian reformed the provincial administration and abolished all vicariates in 535 A.D., he replaced the vicars of the Anastasian Wall with praetor Iustinianus Thraciae (Nov. Iust., XXVI – a. 535). Next year, the emperor created the peculiar post of quaestor Iustinianus exercitus (Nov. Iust., XLI). The territory of the quaestura contained the provinces Moesia Secunda and Scythia Minor, located in the lower Danube region, as well as the provinces of Cyprus, Caria and the Aegean Islands. In turn, the responsibilities of the Praetor of Thrace were confined to the region of the Anastasian Wall. The new post combined the functions of military officer and head of civil administration. The nature of praetor Thraciae is discussed in the light of Nov. Iust., XXVI and compared with analogous praetors established in the provinces of Paphlagonia and Pisidia (Nov. Iust., XXIV–XXV), as well as other data. After the fall of John of Cappadocia in 541, Justinian revoked some administrative reforms, restoring the vicariate of Pontica and restoring former powers to the comes Orientis who played the same role as a vicar in the Diocese of Oriens. In the Balkans, Justinian left the post of quaestor Iustinianus exercitus intact. Meanwhile, the function of the preator Thraciae, which proved to be inefficient, as the incursions of the Slavs (ca. 550) and the Kutrigur Bulgars in 559 had shown, was possibly abolished. The repairs of the Anastasian Wall needed to be conducted after the great earthquake in 557 A.D. by Justinian himself, which indirectly demonstrates the weakness of administration under praetor Thraciae or the earlier abolishment of the post. It is likely that instead Justinian reinstated the post of the vicar of Thrace, who became a civil administrator over the part of the former Diocese of Thrace limited to the provinces of Europa, Haemimontus, Rhodopa and Thracia, a function which was probably more suited to overseeing construction undertakings conducted at the time in the Balkans.